2016
DOI: 10.1111/jcpe.12571
|View full text |Cite
|
Sign up to set email alerts
|

A 5‐year prospective study on single immediate implants in the aesthetic zone

Abstract: Single immediate implants showed high implant survival and limited marginal bone loss in the long term. However, mid-facial recession, mid-facial contour and alveolar process deficiency deteriorated after 1 year. With an aesthetic complication rate of 8/17 in well-selected patients who had been treated by experienced clinicians, type I placement may not be recommended for daily practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
240
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(273 citation statements)
references
References 37 publications
(36 reference statements)
19
240
2
4
Order By: Relevance
“…[12][13][14] Possible explanations may be a stringent selection ridges, yet only short-term data were published. [12][13][14] Possible explanations may be a stringent selection ridges, yet only short-term data were published.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] Possible explanations may be a stringent selection ridges, yet only short-term data were published. [12][13][14] Possible explanations may be a stringent selection ridges, yet only short-term data were published.…”
Section: Discussionmentioning
confidence: 99%
“…2,7,8 demonstrated stable hard and soft tissues, and pleasing aesthetics at 6 years of follow-up for early implant placement (type II) and concomitant contour augmentation with guided bone regeneration. 11,12 In addition, Benic et al (2012) demonstrated an incomplete buccal bone wall in 5/14 patients who had been treated with an immediate implant 7 years earlier. Low risk for midfacial recession has also been reported for ridge preservation and single implant treatment in a delayed approach.…”
Section: Introductionmentioning
confidence: 99%
“…11 The necessity of a facial bony wall as a prerequisite for immediate insertion has been discussed controversially. 15,16 To the best of our knowledge, there is only one study that explored the relationship between labial tissue thickness and buccolingual implant angulation. 12,13 On the other hand, an influence of the extent of the facial bone defect and the alignment on the resulting facial soft tissue level have been documented.…”
Section: Introductionmentioning
confidence: 99%
“…Following these studies, clinical research has been focused on improving the esthetic outcome of immediate implant placement. Results from clinical studies have shown a high risk of midfacial recession following immediate implant placement in cases of an incomplete buccal bone wall . However, case series studies have reported reconstitution of the absent labial bone plate through different techniques .…”
Section: Introductionmentioning
confidence: 99%